2023
DOI: 10.1101/2023.10.13.562225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Actin-based deformations of the nucleus control multiciliated ependymal cell differentiation

Marianne Basso,
Alexia Mahuzier,
Ana-Maria Lennon-Duménil
et al.

Abstract: Ependymal cells (ECs) are multi-ciliated cells in the brain that contribute to cerebrospinal fluid flow. ECs are specified at embryonic stages but differentiate and grow cilia later in development. Differentiation depends on genes such as GEMC1 and MCIDAS with E2F4/5 but also on cell cycle related factors. In the mouse brain, we observe that nuclear deformation accompanies EC differentiation. Tampering with these deformations either by decreasing F-actin levels or by severing the link between the nucleus and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…4C and D ). We also stained WT and Cena KO cultures for retinoblastoma protein phosphorylation (pRB pSer807/811), another hallmark of cycling cells entering S-phase (Zhou et al, 2022), which was recently shown to also turn positive during early MCC differentiation (Basso et al, 2023; Ortiz-Alvarez et al, 2022). Consistent with the p27 observations, while the proportion of pRB+ cells begins to increase in FOXJ1+ WT cells entering A-stage (:: 26%), very few cells are pRB+ in FOXJ1+ Cena KO cells (:: 3%), a proportion comparable to the proportion observed in WT FOXJ1+ cells at the centrosome stage (:: 4%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4C and D ). We also stained WT and Cena KO cultures for retinoblastoma protein phosphorylation (pRB pSer807/811), another hallmark of cycling cells entering S-phase (Zhou et al, 2022), which was recently shown to also turn positive during early MCC differentiation (Basso et al, 2023; Ortiz-Alvarez et al, 2022). Consistent with the p27 observations, while the proportion of pRB+ cells begins to increase in FOXJ1+ WT cells entering A-stage (:: 26%), very few cells are pRB+ in FOXJ1+ Cena KO cells (:: 3%), a proportion comparable to the proportion observed in WT FOXJ1+ cells at the centrosome stage (:: 4%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%